Developing a Latino-Adapted Parenting Program for Primary Care: A Delphi Study - Haralson, David M. (East Carolina University, 2018)
Latino children suffer from many health disparities compared to their non-Latino peers. One way to minimize these health disparities is by empowering Latino parents through parenting support programs. Primary care agencies, the location where most Latino families prefer to have their physical and mental health care needs met, remain an ideal setting for implementing such parenting programs. However, little to no research has been completed on how to adapt existent primary care parenting programs to the beliefs, values, and practices of Latino families. The first manuscript is a conceptual paper which adds to the cross-cultural and community health literature by comparing existing primary care parenting programs, evaluating how well-adapted they are to the cultural needs of Latino families, and offering suggestions for further improvement. The findings from this study demonstrated that parenting programs that are implemented in primary care settings are severely lacking in their Latino cultural adaptations.
Keywords: Latino; Primary Care; Parent Education; Hispanic American parents--Health and hygiene; Parents--Services for; Hispanic American families--Social life and customs